Transcriptional factor OmpR positively regulates prodigiosin biosynthesis in Serratia marcescens FZSF02 by binding with the promoter of the prodigiosin cluster - Jia, Xianbo; Zhao, Ke; Liu, Fangchen; Lin, Junjie; Lin, Chenqiang; Chen, Jichen (Frontiers in Microbiology, 2022)
Abstract: Prodigiosin is a promising secondary metabolite mainly produced by S. marcescens. The production of prodigiosin by S. marcescens is regulated by different kinds of regulatory systems, including the EnvZ/OmpR system. In this study, we demonstrated that the regulatory factor OmpR positively regulated prodigiosin production in S. marcescens FZSF02 by directly binding to the promoter region of the prodigiosin biosynthesis cluster with a lacZ reporter assay and electrophoretic mobility shift assay (EMSA). The binding sequence with the pig promoter was identified by a DNase I footprinting assay. We further demonstrate that OmpR regulates its own expression by directly binding to the promoter region of envZ/ompR. For the first time, the regulatory mechanism of prodigiosin production by the transcriptional factor OmpR was revealed.